2010
DOI: 10.1038/ng.717
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis increases to 71 the number of confirmed Crohn's disease susceptibility loci

Abstract: We undertook a meta-analysis of six Crohn's disease genome-wide association studies (GWAS) comprising 6,333 affected individuals (cases) and 15,056 controls and followed up the top association signals in 15,694 cases, 14,026 controls and 414 parent-offspring trios. We identified 30 new susceptibility loci meeting genome-wide significance (P < 5 × 10⁻⁸). A series of in silico analyses highlighted particular genes within these loci and, together with manual curation, implicated functionally interesting candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
1,920
4
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 2,308 publications
(2,020 citation statements)
references
References 52 publications
60
1,920
4
18
Order By: Relevance
“…As the identification of NOD2/CARD15 as the first susceptibility gene for CD, an intriguing hypothesis was raised, suggesting that genetic variations in other receptors of the innate immune system may contribute to CD susceptibility. Genome-wide association studies have identified multiple susceptibility loci involved in the genetic susceptibility to CD, 23,24 and they have confirmed the main role of the innate immunity in the disease. However, these loci explain about only the 10% of the overall variance in disease risk, which may be as much as a fifth of the genetic risk, suggesting that many additional loci are yet to be identified.…”
Section: Discussionmentioning
confidence: 87%
“…As the identification of NOD2/CARD15 as the first susceptibility gene for CD, an intriguing hypothesis was raised, suggesting that genetic variations in other receptors of the innate immune system may contribute to CD susceptibility. Genome-wide association studies have identified multiple susceptibility loci involved in the genetic susceptibility to CD, 23,24 and they have confirmed the main role of the innate immunity in the disease. However, these loci explain about only the 10% of the overall variance in disease risk, which may be as much as a fifth of the genetic risk, suggesting that many additional loci are yet to be identified.…”
Section: Discussionmentioning
confidence: 87%
“…3 Therefore, large sample sizes are required and many collaborations have been established to achieve this, resulting in published metaanalyses for a range of diseases and traits. [4][5][6][7][8] One standard quality-control measure for GWAS and meta-analysis is genomic control (GC). [9][10][11] The concept behind this method is that apart from a small number of SNPs that show a true association with the trait or disease, the test statistics for other SNPs should follow the distribution under the null hypothesis of no association between a SNP and the trait.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of genetic associations in Crohn's disease (CD) and ulcerative colitis (UC) have identified polymorphisms in or near genes central to CD4? T cell function, such as the receptor for interleukin (IL)-23 [1], a cytokine essential for the survival of the Th17 subset of CD4? T cells, which is implicated in the pathogenesis of several animal models of autoimmunity [2].…”
mentioning
confidence: 99%